Efektivitas Media E-Paper Sebagai Wahana Produktifitas Meningkatkan Kemampuan Menulis Cerita Moral - Sisi Rosida (Balai Bahasa Sumatera Utara, 2021)
Learning literature in the digital form makes instilling character values in students easier. Learning to write moral stories as a potential alternative to imitating good behavior may foster literary appreciation through the publication of the results of writing moral stories. This study examined the effectiveness of e-paper in improving the ability to write moral stories and students’ productivity in learning. The type of this study was quantitative-descriptive research using a pre-experimental design, specifically in the form of a one-group pretest-posttest design. In this study, data were collected using a written test and documentation. The results showed that (1) e-paper was effective in improving the ability to write moral stories. (2) the learning process involved e-paper as a medium for student productivity in writing moral stories, as reviewed from students’ learning outcomes published in the mass media.